2012
DOI: 10.1016/j.biomaterials.2011.09.058
|View full text |Cite
|
Sign up to set email alerts
|

Modulation of osteogenic differentiation in hMSCs cells by submicron topographically-patterned ridges and grooves

Abstract: Recent studies have shown that nanoscale and submicron topographic cues modulate a menu of fundamental cell behaviors, and the use of topographic cues is an expanding area of study in tissue engineering. We used topographically-patterned substrates containing anisotropically-ordered ridges and grooves to investigate the effects of topographic cues on mesenchymal stem cell morphology, proliferation, and osteogenic differentiation. We found that human mesenchymal stem cells cultured on 1400 or 4000 nm pitches sh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

12
190
1
1

Year Published

2013
2013
2020
2020

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 213 publications
(204 citation statements)
references
References 43 publications
12
190
1
1
Order By: Relevance
“…Alternatively, decades of research have shown that surface topography can directly stimulate bone cell differentiation and function on various material substrates, including polymers (Fu et al, 2010;Watari et al, 2012;Wilkinson et al, 2011;You et al, 2010), titanium (Brunette, 1988;Gittens et al, 2011;, ceramics (Webster, 2000;Zhang et al, 2014), and tissue (Gray et al, 1996). Topographical control of cell fate is a complex phenomenon that can occur through focal adhesion clustering and downstream focal adhesion kinase (FAK) signalling (McNamara et al, 2010).…”
Section: Nl Davison Et Almentioning
confidence: 99%
“…Alternatively, decades of research have shown that surface topography can directly stimulate bone cell differentiation and function on various material substrates, including polymers (Fu et al, 2010;Watari et al, 2012;Wilkinson et al, 2011;You et al, 2010), titanium (Brunette, 1988;Gittens et al, 2011;, ceramics (Webster, 2000;Zhang et al, 2014), and tissue (Gray et al, 1996). Topographical control of cell fate is a complex phenomenon that can occur through focal adhesion clustering and downstream focal adhesion kinase (FAK) signalling (McNamara et al, 2010).…”
Section: Nl Davison Et Almentioning
confidence: 99%
“…In particular, there has been increasing interest in developing smart scaffolds mimicking the extracellular matrix, in order to favor long-term cell grafting. 1 Structural design of biomimetic scaffolds has been improved at the micro-and nanoscale using designed nanostructures, from nanofibers, 2,3 to nanogrooves, 4,5 and using different nanomaterials such as carbon nanotubes 6,7 and graphene material. 8,9 Nanotechnologies like nanoparticles or nanoreservoirs have also been introduced for the bioactivation of the scaffolds through the controlled release of bioactive therapeutics.…”
Section: Introductionmentioning
confidence: 99%
“…To overcome the complications associated with these methodologies (site morbidity, limited availability and host tissue reactivity), cell-based tissue engineering strategies using sophisticated biomaterials have been developed and represent a promising part of the regenerative medicine field. In the recent years, a plethora of advanced biomaterials mimicking extracellular matrix were designed based on the micro-and nano-scale environment of tissues, using nanotechnologies as graphene, nanogrooves and carbon nanotubes [1][2][3][4][5][6][7][8]. More recently, and with the development of the third generation materials, there has been increasing interest in developing nanoparticles and nanoreservoirs containing active molecules able to bio-activate scaffolds [9][10][11][12][13][14].…”
Section: Introductionmentioning
confidence: 99%